The Mismeasure of Manabozho: Unsettling the Science of the Mind in Henry R. Schoolcraft’s Algic Researches - Orr, Ittai (American Literary History, 2023)
Abstract This article recovers early Native American writing that challenges the premises of nineteenth-century mental science and its support for colonialism. It demonstrates how the manuscripts and correspondences of Irish-Ojibwe poet Jane Johnston Schoolcraft and her brother William Johnston, particularly Johnston’s translation of the Anishinaabe story of the simultaneously clever and foolish trickster Manabozho, contradict the ethnological speculations and editorial alterations made by Henry Rowe Schoolcraft, Jane’s husband and William’s employer, in his Algic Researches (1839). Henry sought to prove that Native Americans were intellectually stagnant, but Jane and William provided him with Ojibwe and Ottawa stories that promote collective adaptability and resilience. This collectivism is a useful hermeneutic through which to interpret Jane’s struggle with “melancholy thoughts” expressed in two drafts of her poem “The Contrast.” Instead of reading Jane as an Indigenous poet staggered by European knowledge, as Henry posits, scholars can more accurately root her mental state in the fragility of her kinship network during high-stakes treaty negotiations facilitated by her absent husband. This reexamination of the Johnston-Schoolcraft papers aids efforts to decolonize mental health, madness, and disability by piecing together Jane and William’s use of stories as equipment for living during a consequential period of transition for the Anishinaabe of present-day Michigan.In contrast to Henry’s project of evaluation and disqualification, William and Jane collected and shared their stories for their own project of preservation, carrying forward the recognition those tales invite that well-being and health are attributes of collectives rather than individuals.